KARAKTERISTIK ARUS BOCOR-TEGANGAN ARESTER SiC - , GESANG NDARU PRAYOGO; , Prof. Dr. Ir. T. Haryono, M.Sc., C.Eng., MIET. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia is a tropical country. It often occurs lightning strikes. Electrical power system equipment is very susceptible to lightning strikes. Therefore, the insulation system against lightning strikes is important. The tools used to protect power systems from lightning strikes is arrester. Arrester has a very important role in power system. Arrester is needed to protect electrical equipment from the dangers due to overvoltage caused lightning strikes. Overvoltage that occurs can cause damage to electrical equipment. Arrester that is often used is made of silicon carbide ( SiC ) . This test aims to determine the effect of changes in temperature and humidity on leakage current-voltage characteristics of SiC arrester. Testing were done by providing a high voltage AC on SiC arrester at a certain temperature and humidity. The test results showed changes in temperature and humidity affect the leakage current-voltage characteristics of SiC arrester. The temperature rise is inversely proportional to the value of leakage current . When the temperature rises, the value of the leakage current becomes small. While the increase in humidity is directly proportional to the value of leakage current. When the humidity rises , the value of the leakage current becomes large. This occurs because of the temperature and humidity affect the value of the resistance of SiC arrester block. Largest leakage current value is obtained when the temperature is 20Â° C at a humidity of 90 % , amounting to 6.6 mA with input voltage 3 kV. And the smallest value of leakage current is obtained when the temperature is 60Â° C at a humidity of 40 % , amounting to 2,1 mA with input voltage 3 kV. It can be concluded that the largest leakage occurs when the lowest temperature with the highest humidity, and the smallest leakage current occurs when the temperature is highest with the lowest humidity.